Identifying alternative mental health interventions: a systematic review of randomized controlled trials of chanting and breathwork - Malviya, Shikha (Journal of spirituality in mental health, 2022)
This systematic review of randomized controlled trials investigated the effects of two religious/spiritual (R/S) practices (breathwork and chanting) on mental health outcomes (depression, anxiety, stress, and post-traumatic stress disorder (PTSD) symptoms). After registering with PROSPERO (CRD42020136645), a systematic search of four major databases (CINAHL, MEDLINE, PsycINFO, and ProQuest) was undertaken using predetermined eligibility criteria. Quality of included studies was assessed using the PEDro scale and Cochrane risk of bias tool. Although varying in quality, 15 included studies provide moderate to strong support for the effectiveness of chanting and breathwork to alleviate anxiety, depression, stress, and symptoms of PTSD.